A Cytotaxonomic Survey of the Genus Melanophryniscus Gallardo, 1961 (Anura: Bufonidae) - Baldo, Diego; Cotichelli, Leonardo; Pereyra, Martin O.; Borteiro, Claudio; Netto, Flavia; Kolenc, Francisco; Brusquetti, Francisco [UNESP]; Bidau, Claudio (Soc Study Amphibians Reptiles, 2012)
We present a cytogenetic survey of the basal bufonid genus Melanophryniscus that covered 14 of the 25 species currently recognized, representing the three phenetic species groups: M. moreirae, M. stelzneri, and M. tumifrons. All species presented a diploid chromosome complement constituted by 11 bi-armed chromosome pairs (2n = 2x = 22; FN = 44). Some remarkable differences were observed between species groups: chromosome pair 4 was metacentric in species of the M. tumifrons group (also with a distinctive C-positive block) but submetacentric in the M. stelzneri group and M. sanmartini (M. moreirae group); pair 5 was submetacentric in M. sanmartini and metacentric in the rest. Chromosome secondary constrictions and silver-stained nucleolar organizer regions were located either in pair 5, 7, or 8 in the M. tumifrons group, M. sanmartini and M. krauczuki (M. stelzneri group), and M. stelzneri group, respectively; and pair 7 was relatively larger in M. sanmartini and M. krauezuki. Studied cytogenetic characters support the M. tumifrons group and suggest a close relationship between M. krauczuki and M. sanmartini. These results call for a reassessment of species relations within Melanophryniscus under an inclusive phylogenetic study.